Academic Business Incubators as a Tool in Implementing Entrepreneurship Education – Theoretical Approach - Budac Camelia; Ilie Livia (Studies in Business and Economics, 2024)
In recent years, in order to stimulate economic growth, the importance of innovation and entrepreneurship has been increasingly recognized by practitioners and teaching staff. Universities must contribute to this growth, as a center of knowledge creation and a center of research. However, transforming academic research into marketable products and services faces significant challenges. Addressing these challenges has necessitated the emergence of academic incubators as an essential mechanism for providing resources, support, and an environment suitable for the development of startups. Thus, academic incubators are becoming an essential component of a university in order to recruit and retain students, instructors, and researchers with an entrepreneurial mindset, as well as to stay exposed to students who are becoming more and more interested in starting enterprises or social projects. In these conditions, the present paper aims to provide an overview of the role of academic incubators in stimulating innovation and entrepreneurship in universities, emphasizing their role, functions and impact in the socio-economic environment.